Creative writing teaching techniques on the development of written expression - Chasi-Solórzano, Byron (2025)
The scarce application of creative writing teaching techniques due to multiple factors contributes to a weak learning of written expression. Therefore, it is essential to investigate various techniques that promote the development of written expression. The objective of this research was to evaluate the effects of creative writing teaching techniques on the development of written expression in General Basic Education (EGB) students. The application of innovative teaching techniques requires that teachers commit themselves to improve and innovate their practices. For this purpose, a quantitative approach was used, with a quasi-experimental pre-post test design at a correlational level. The sample consisted of 20 intentionally selected 8th grade EGB students. Classes were designed in which creative writing teaching techniques were applied and the development of written expression was measured using an observation sheet with 5 dimensions and 20 indicators. The main finding is that creative writing techniques significantly improve students' written expression. It is concluded that the intervention favored aspects such as spelling, sequence and order, calligraphy, and stimulated narrative creativity allowing students to present innovative ideas that promoted divergent thinking. In addition, students were able to communicate ideas with greater clarity and coherence, using a linguistic register appropriate to the communicative situation. The implication of these results is that the incorporation of innovative teaching techniques contributes to a substantial improvement in written expression.